LO019: The prevalence and characteristics of non-transported EMS patients in Nova Scotia. (2nd June 2016) - Carrigan, S.A.; Asada, Y.; Travers, A.; Goldstein, J.; Carter, A.
Abstract : Introduction: An undefined yet potentially significant risk for Emergency Medical Services (EMS) systems are patients who access 911 with an ambulance response who are not transported to hospital (non-transport). Our objective was to determine the prevalence and associated characteristics of non-transport and potentially clinically adverse non-transports in Nova Scotia.Methods: We conducted a secondary analysis of pooled cross-sectional, population-based administrative data in a provincial EMS system that provides care to 920, 000 residents. Electronic patient care record (ePCR) data was retrospectively analyzed for one calendar year (2014). The dependent variables were non-transport status and potentially adverse non-transport status. Potentially adverse non-transports were defined as a repeat call within 48 hours for a related complaint with the outcome of transport or death. Independent variables include patient characteristics, (age, sex, vitals and paramedic clinical impression), operational (crew type and response code) and environmental (time, date, and location). For both objectives we determined the prevalence of the outcome of interest, and associated characteristics.Results: There were 74, 471 EMS responses between January to December 2014, 18.9% (n=14, 094/74, 471) resulted in a non-transport. The characteristics most associated with non-transport are: age, paramedic clinical impressions, number of co-morbidities, response mode, and incident location type. As age decreased, the likelihood of non-transport increased. Younger non-transported patients (0-15 years old) (OR 2.2, 99.9% CI 1.9-2.5) are more likely to have non-transport. Relative to other paramedic clinical impressions, glycemic issues (OR 4.8; 99.9% CI 3.9-5.7) and wellness checks (OR 6.5; 99.9% CI 5.7-7.3) are more likely to have a non-transport. Non-transports are more likely at a detention facility (OR 4.1; 99.9% CI 3.2-5.1) or a roadway (OR 2.4; 99.9% CI 2.1-2.8). 5.6% (n=798/14094) of non-transport patients were classified as a potentially adverse non-transport.Conclusion: This study demonstrated that a significant portion of patients (18.9%) had a non-transport outcome, but only a small percentage (5.6%) were considered potentially adverse. The results of this study provide timely information to policy makers and healthcare practitioners on the scope of this issue, and suggest potential directions for future study and clinical decision making.